RIBA DAN PEMBIAYAAN DALAM KONSEP HINDU - Putra, I Nyoman Nugraha Ardana (Jurnal Keuangan dan Perbankan, 2015)
This research aimed to explorer usury and  financing concept of  hinduism by hermeneutic research. In order that,  data collection  in this research used documentation in hinduism manuscript as Manawa Dharmasastra and Artha Sastra. Data validation using indeepth the interview conducted literary expert, Hindu philosopher and humanist. The result shows that the concept of usury is the way of financing not opposite with dharma and  financing in Hinduism actually explain the interest rate 2 percent until 5 percent.